Pengaruh Price Earning Ratio, Debt To Equity Ratio, Return On Asset, Current Ratio Dan Firm Size Terhadap Nilai Perusahaan - Pasaribu, Ruth Mita Tettyana Br.; Situmorang, Saida; Sagala, Rina Fitrayani; Sitorus, Jessy Safitri; Masnaya, Muthmainnah (Universitas Gorontalo, 2023)
The company is an organization that has a goal of obtaining sustainable profits. This study aims to analyze the effect of the Price Earning Ratio, Debt To Equiy Ratio, Return On Assets, Current Ratio and Firm Size on Company Value in Real Estate Companies and the Property Sector on the IDX in 2018-2020. The sample selection used purposive sampling with a total sample of 111, which was processed using the SPSS application. The test results explain that the Debt To Equity Ratio, Price Earning Ratio, Current Ratio, Firm Size and Return On Assets have a simultaneous effect on company value in Real Estate and Property companies on the IDX in 2018-2020. Return On Assets, Price Earning Ratio, and Current Ratio do not partially affect Company Value in Property and Real Estate companies in 2018-2020. Firm Size and Debt to Equity Ratio have a partial effect on Firm Value in Real Estate and Property companies on the IDX in 2028-2020.